PROBIOTICS DELIVERY: DOES THE MATRIX MATTER?. (July 2016) - Marzorati, M.
Abstract : Probiotics can be defined as live microorganisms which when administered in adequate amounts confer a health benefit to the host. Two crucial aspects determining the success of a probiotic treatment are the resistance of the bacteria to stomach acids and bile salts in the upper gastrointestinal tract (GIT) and their capacity to compete with the indigenous microbiota in the colon by eventually adhering to the mucus layer covering the gut wall. If these requirements are fulfilled, successful colonization of the intestinal tract can be expected, which might then result in beneficial effects on human health. The capacity to colonize the gastrointestinal tract is largely depending on the intrinsic characteristics of the probiotic strains (e.g. acid and bile tolerance), yet also on the specific formulation in which they are delivered to the gut. Formulations which protect the bacteria from the harsh conditions in the stomach and small intestine allow the probiotics to reach the colon under optimal conditions, which will of course allow more efficient competition with the resident microbial community. The Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) has been used to assess how microencapsulation, gastric resistant capsules and food matrices (i.e. fermented milk or chocolate) can enhance the survival of the probiotic strains during the transition in the upper GIT under either fasted or fed conditions.